Implementasi Logika Fuzzy Dalam Menentukan Jumlah Produksi Pembuatan Kain Dengan Metode Mamdani - Tri Ramdhany (LPKIA, 2023)
In connection with the development of the company's industry which is increasingly advanced in fierce business competition, many companies are using strategies to be able to compete with other companies. Companies want maximum profit from production. If you experience a loss, it will be a big problem for the company to produce. When profit is maximum, there is maximum production. Fuzzy is known to be able to map an input into an output without ignoring the existing factors. Fuzzy is very flexible with existing data and can have tolerance for that data. This study results from the fuzzy Mamdani method predicting 5 items, for the accuracy of the Mamdani fuzzy calculation with the previous production result of 64.8% of the results of the Mamdani fuzzy calculation. For further research to be more effective in calculations, more complete and supporting data are needed that can help Mamdani fuzzy calculations. Keywords: Fuzzy, Production, Algorithm, fuzzy Mamdani